Handbook of visual communication
1 online resource.
Keywords: "This Handbook of Visual Communication explores the key theoretical areas and research methods of visual communication. With chapters contributed by many of the best-known and respected scholars in visual communication, this volume brings together significant and influential work in the discipline"--